Artistic Attitude on the Instrument of Medicine in Iran during the Qajar Dynasty,with Emphasis on Metal Works in Tehran Museums - Mina Shariati NAJAF ABADI; Abdolkarim ATTARZADEH (国际转化医学杂志（英文版）, 2019)
The medical instrument is one of the first tools that human make it to relieve of pain. Medical also is the ancient human practice which has been developed by trial and error, and transfer of scientific knowledge of research and innovation in this area. The medical instruments in the Qajar period was simple but had a good shape with different paterns. The use of art in traditional medicine devices was a healing and learning approach and provided solace in the patient. Our aim is to show the relation between medical and art and the infuence of art in medicine. This study also aims to understand the companionship of traditional arts and ancient medical instruments and to rehabilitate them. In addition, the construction, decorations and forms of medical tools in Qajar period have been reviewed. In this paper, related documents have been collected based on observation in medical instruments available in Tehran museums and libraries. The design and metal carving paterns on these instruments may cause a mental and spiritual aspect and feel of peace in the patient.